1995
DOI: 10.1037/0033-295x.102.4.652
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy of personality judgment: A realistic approach.

Abstract: The "accuracy paradigm" for the study of personality judgment provides an important, new complement to the "error paradigm" that dominated this area of research for almost 2 decades. The present article introduces a specific approach within the accuracy paradigm called the Realistic Accuracy Model (RAM). RAM begins with the assumption that personality traits are real attributes of individuals. This assumption entails the use of a broad array of criteria for the evaluation of personality judgment and leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

99
1,481
0
33

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,213 publications
(1,613 citation statements)
references
References 165 publications
(249 reference statements)
99
1,481
0
33
Order By: Relevance
“…Such a gold standard can be approximated by either observer or self-reports, however it is likely that for a specific trait one type of report will be closer to the true personality. A hypothesis that remains to be tested is that traits with a high visibility (e.g., extraversion) are more accurately assessed using observer reports, as they tend to yield a higher interjudge agreement (Funder, 1995), while low visibility traits (e.g., emotional stability) are better assessed by oneself. A personality recogniser aiming to estimate the true personality would therefore have to switch from observer models to self-report models, depending on the trait under assessment.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Such a gold standard can be approximated by either observer or self-reports, however it is likely that for a specific trait one type of report will be closer to the true personality. A hypothesis that remains to be tested is that traits with a high visibility (e.g., extraversion) are more accurately assessed using observer reports, as they tend to yield a higher interjudge agreement (Funder, 1995), while low visibility traits (e.g., emotional stability) are better assessed by oneself. A personality recogniser aiming to estimate the true personality would therefore have to switch from observer models to self-report models, depending on the trait under assessment.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…This research suggests that the ease of trait judgment and trait visibility is associated with self-other personality agreement (Funder and Colvin 1997;Hays and Dunning 1997). As defined by Funder (1995), ''good'' traits are those providing raters with frequent cues regarding the target's standing on the personality dimension. For example, Barrick et al (2000) found agreement was higher between self-ratings and interviewer-ratings on traits that were easier to judge because they were more observable in an interview (e.g., extraversion, openness to experience) compared to less visible, internal traits (e.g., neuroticism).…”
Section: Reliability and Validity Of Recruiters' Inference Makingmentioning
confidence: 94%
“…This result is not surprising given that people who keep secrets generally do their best to prevent others from finding out about the information they try to conceal. In this sense, concealment is not what Funder (1995) calls a good behavior. Concealment is a behavior that people avoid displaying overtly, that they try to disguise and actively prevent others from discovering.…”
Section: Perceiving Concealment In Close Relationshipsmentioning
confidence: 99%